Effects of two kinds of vestibular function training on reducing motion sickness in college students - Linyao Shi; Jing Zhao; Jiamei Lu; Chuanxia Cao; Qikun Zhang; Chuanjing Qiu; Zhanguo Jin; Shengguang Yan; Shengguang Yan; Shengguang Yan (Frontiers in Neurology)
IntroductionTo explore the advantages and disadvantages of different vestibular function training to improve Motion sickness (MS) can be associated with significant symptoms, including fatigue, dizziness, headaches, nausea, and vomiting. Vestibular function training has increasingly replaced MS medications over the past few years and has almost no side effects.MethodsWe selected 109 students with MS from a university in Tangshan, China, and randomly assigned them to either an electric rotating chair group or a visual-motion cage rotating chair group. Both training groups underwent vestibular function training for 90 seconds a day for seven consecutive days.ResultsAfter training, both groups’ Graybiel scores, blood pressure, high-frequency power (HF), and root mean square of successive differences (rMSSD) between adjacent normal heartbeats significantly decreased. In the visual-motion cage rotating chair group, in addition to a reduction in the percentage of adjacent normal-to-normal intervals which differed by more than 50 ms (pNN50), as well as decreases in low-frequency power (LF), an increase in LF/HF was observed. Between-group comparisons showed that the Graybiel scores in the electric rotating chair group were better than those in the visual-motion cage rotating chair group. When the two groups were stratified into high and low-susceptibility subgroups, the low-susceptibility subgroup of the electric rotating chair group had lower Graybiel scores and diastolic blood pressures than the low-susceptibility visual-motion cage rotating chair subgroup, whereas in the high susceptibility subgroup, LF, rMSSD, and pNN50 were significantly higher in the visual-motion cage rotating chair group than in the electric rotating chair group.DiscussionThis study compared the effects of two types of vestibular function training on Graybiel scores and heart rate variability (HRV). we found that seven days of training with both the electric rotating chair and the visual-motion cage rotating chair relieved MS symptoms and enhanced sympathetic regulation. In terms of improving the subjective degree of MS, the electric rotating chair was superior to the visual-motion cage rotating chair. Subgroup analysis results showed that low-susceptibility MS patients’ symptoms were better relieved with electric rotating chair training, while high-susceptibility patients’ symptoms were better relieved with visual-motion cage rotating chair training.